2023
DOI: 10.18421/tem122-38
|View full text |Cite
|
Sign up to set email alerts
|

Trend and Visualization of Artificial Intelligence Research in the Last 10 Years

Abstract: Technology is permeating every aspect of our everyday lives, and businesses are increasingly turning to learning algorithms. These technologies are commonly associated with Artificial Intelligence (AI), Deep Learning (DL), Machine Learning (ML), and Artificial Neural Network (ANN). Due to previous research exciting findings, implications, and limitations, the research publication on AI, ML, DL, and ANN will increase each year. Finally, the growth analysis of AI, ML, DL, and ANN publications in last 10 years br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…These studies included the integration of management and digital technology for Indonesia's educational progress (Sumarno, 2023), learning management systems in learning assessment for operations management courses (Strakos et al, 2023), integration of artificial intelligence (AI) ChatGPT in university students in Thailand (Fuchs & Aguilos, 2023), a survey of knowledge, attitudes, and practices of teachers in the Philippines, using ChatGPT (Robledo et al, 2023), and the views of higher education stakeholders regarding the ethics of using AI in distance learning (Holmes et al, 2023). While research on the topic of digital learning management using artificial intelligence ChatGPT with systematic literature review (SLR) techniques and similar ones found research on the implementation of AI for health care with SLR (Loh et al, 2022), AI in machine learning with a bibliometric review (Shamima et al, 2022), a systematic review of artificial intelligence in midwifery and nursing (Siobhán O'Connor et al, 2022), bibliometric and content analysis in online learning in management education (Ng et al, 2023), a systematic review of digital learning theories with e-Learning for nursing and midwifery courses (Siobhan O'Connor et al, 2023), review and taxonomy of ChatGPT in healthcare (Jianning Li et al, 2023), review and taxonomy of ChatGPT in healthcare (Prananta et al, 2023), impact of ChatGPT implementation for students with SLR techniques (Renato et al, 2023), use of ChatGPT in software companies with an initial systematic literature review (Pattyn, 2023), SLR on Chatbot implications for customer satisfaction (Daza et al, 2023), research on visualization and AI trends over the past decade (Prahani et al, 2023), research into the impact of ChatGPT use in education using systematic review techniques (Montenegro-Rueda et al, 2023), and SLR on ethics in learning using ChatGPT (Vargas-Murillo et al, 2023). Among these studies, no research has been found on digital learning management using OpenAI ChatGPT in education with SLR techniques.…”
Section: Introductionmentioning
confidence: 99%
“…These studies included the integration of management and digital technology for Indonesia's educational progress (Sumarno, 2023), learning management systems in learning assessment for operations management courses (Strakos et al, 2023), integration of artificial intelligence (AI) ChatGPT in university students in Thailand (Fuchs & Aguilos, 2023), a survey of knowledge, attitudes, and practices of teachers in the Philippines, using ChatGPT (Robledo et al, 2023), and the views of higher education stakeholders regarding the ethics of using AI in distance learning (Holmes et al, 2023). While research on the topic of digital learning management using artificial intelligence ChatGPT with systematic literature review (SLR) techniques and similar ones found research on the implementation of AI for health care with SLR (Loh et al, 2022), AI in machine learning with a bibliometric review (Shamima et al, 2022), a systematic review of artificial intelligence in midwifery and nursing (Siobhán O'Connor et al, 2022), bibliometric and content analysis in online learning in management education (Ng et al, 2023), a systematic review of digital learning theories with e-Learning for nursing and midwifery courses (Siobhan O'Connor et al, 2023), review and taxonomy of ChatGPT in healthcare (Jianning Li et al, 2023), review and taxonomy of ChatGPT in healthcare (Prananta et al, 2023), impact of ChatGPT implementation for students with SLR techniques (Renato et al, 2023), use of ChatGPT in software companies with an initial systematic literature review (Pattyn, 2023), SLR on Chatbot implications for customer satisfaction (Daza et al, 2023), research on visualization and AI trends over the past decade (Prahani et al, 2023), research into the impact of ChatGPT use in education using systematic review techniques (Montenegro-Rueda et al, 2023), and SLR on ethics in learning using ChatGPT (Vargas-Murillo et al, 2023). Among these studies, no research has been found on digital learning management using OpenAI ChatGPT in education with SLR techniques.…”
Section: Introductionmentioning
confidence: 99%